Implementation Of Aqidah Akhlak Education In Enhancing Students' Tolerance Character In Islamic Boarding Schools - Zuhri, M. Syaifudin; Saini, Mukhamat (IERA, Islamic Education and Research Academy, 2023)
This study aims to explore the implementation process of Aqidah Akhlak education in enhancing students' tolerance character, identify the supporting factors in the learning process, and evaluate the outcomes of its implementation. This qualitative research utilizes interviews, observations, and documentation for data collection, while data analysis is conducted through data processing and field analysis. The findings indicate that the Aqidah Akhlak education at Madin Al Muhajirin Termas is conducted effectively, following the curriculum and lesson plans which include opening, core, and closing activities with a focus on habituation and role-modeling methods. The habituation method fosters good habits among students, cultivating noble character and tolerance, while role-modeling by teachers further reinforces these values. Supporting factors include regular activities such as group Qur'an recitation, communal prayers, and morning routines involving Asmaul Husna recitations and short surah readings. The implementation of these methods has positively impacted students' ability to respect differences, show courtesy towards teachers, assist peers, and adhere to school regulations